Iatrogenic dissection during neurointerventional procedures: a retrospective analysis. (27th September 2011) - Paramasivam, Srinivasan; Leesch, Wolfgang; Fifi, Johanna; Ortiz, Rafael; Niimi, Yasunari; Berenstein, Alejandro
Abstract : Introduction: Retrospective analysis of patients suffering iatrogenic dissection during neurointervention is reported. The circumstances surrounding the occurrence, early detection, clinical course and management options are discussed. Methods and results: 18 iatrogenic dissections over 11 years were retrospectively analyzed. Data were gathered from patient records, run sheets, morbidity records and imaging studies. All procedures were done by operators trained to operate according to institution standards. Total cases were 6981, with 3925 angiograms and 3056 interventions. Incidence was 0.26%, with 0.25% during diagnostic and 0.26% during intervention. 1031 pediatric cases had no dissections. Beyond 35 years, dissection rate increased to 0.35%. There was no difference between men and women. Carotid dissection was more common than vertebral. Most were minimal intimal tear (67%) and others flow limiting (33%). All cases were managed with heparin in the acute stage and later with aspirin and Plavix or Coumadin, except in two cases. Cases having >70% luminal narrowing with poor intracranial cross circulation were stented. None presented with neurologic deficits acutely or on follow-up. 94% of patients were followed for a variable period, with variable imaging modalities, being a retrospective study. Angiogram, MRI brain with MR angiography (MRA), Doppler ultrasonogram and CT angiograms were used for follow-up. There was good outcome in 94% of the followed-up cases. Conclusion: Iatrogenic dissection is a random event with a benign clinical course. Early detection and aggressive management result in excellent outcome. Angiography is the best modality to follow-up. Non-invasive imaging like MRI with MRA and duplex ultrasonography are good tools to follow dissections.